Mothers’ sense of coherence in the face of their children’s struggles with substance abuse : a qualitative study - Rebello, Steven Paul (My University, 2016)
Developing from an apparent relationship between the theme of ill-health in mothers’ experiences of their children’s struggles with substance abuse and the concept of Sense of Coherence, this study focused on how mothers understood, managed, and made meaning of their children’s struggles with substance abuse. Semi-structured interviews were conducted with nine mothers whose young adult children had struggled with substance abuse. A theoretical thematic analysis revealed that the mothers moved between different understandings of their children’s struggles with substance abuse. The externalisation of responsibility was thought to represent a psychological resource which allowed the mothers to cope with feelings of guilt and shame. The mothers’ internalisation of responsibility for their children’s struggles with substance abuse contributed to a pattern of enmeshment, which in turn contributed to the mothers’ neglect of their own needs and well-being. This pattern of enmeshment continued until the mothers experienced a crisis of meaningfulness. This crisis helped the mothers to challenge their guilt and shame and allowed them to access resources which improved their Sense of Coherence and sense of well-being. Spiritual beliefs were found to be a resource that influenced how the mothers understood, managed and made meaning of their children’s struggles with substance abuse. The results of this study contribute to recommendations for organisations and professionals assisting mothers whose children may struggle with substance abuse.